1, 2, 4-Triazolyl-4-acetate: a ditopic ligand combining soft and hard donor sites in homometallic (AgI) and heterometallic (AgI/UVI) coordination polymers. Issue 12 (21st February 2022) - Senchyk, Ganna A.; Lysenko, Andrey B.; Krautscheid, Harald; Rusanov, Eduard B.; Karbowiak, Miroslaw; Domasevitch, Kostiantyn V.
Abstract : A 1, 2, 4-triazol-4-yl-acetic acid ( trGly-H ) was used for the synthesis of Ag I and Ag I /U VI coordination polymers. The composition space diagram was built for the AgNO3 / trGly-H /UO2 (NO3 )2 ·6H2 O system shows the crystallization fields of two Ag I /U VI -compounds were found. Abstract : 1, 2, 4-Triazol-4-yl-acetic acid ( trGly-H ) has been used as a heterobifunctional ligand for preparing homometallic (Ag I ) and heterometallic (Ag I /U VI ) coordination polymers under hydrothermal conditions. Four coordination compounds, [Ag4 ( trGly )4 ]·2H2 O (1 ), [Ag4 ( trGly )2 ( trGly-H )2 ](NO3 )2 ·2H2 O (2 ), [(UO2 )Ag4 ( trGly )4 (NO3 )2 (H2 O)]·4H2 O (3 ) and [(UO2 )2 Ag6 ( trGly )10 ]·7H2 O (4 ), have been synthesized and structurally characterized. Compounds 1 and 2 are similar and consist of tetranuclear [Ag4 ( tr )4 (COO)2 ] secondary building units (SBUs) supported by four [–N–N–] triazole bridges in the Ag4 -cluster plane and two carboxylate functions in the axial positions, which link the rhomboid units together into a thick layer. Addition of uranyl ions in the reaction system leads to compounds 3 and 4, where tr - and –COO − -functional groups are differentiated by their coordination role: tr binds Ag + ions, while –COO − interacts with UO2 2+ . The crystal structure of 3 includes tetranuclear [Ag4 ( tr )4 (NO3 )2 ] units linked by four [–N–N–] triazoles and two nitrate anions above and below the cluster core. In 3, uranium in a pentagonal bipyramidal UO7 arrangement forms "cation–cation" interactions with Ag I centers (the Ag⋯O{U{O distance is short, 2.600 Å). The 3D framework of compound 4 is constructed from hexanuclear [Ag6 ( tr )10 ] SBUs in a form of hexagonal twisted prisms that are further stacked into a column motif through argentophilic (Ag⋯Ag) interactions of 3.06 Å. To explore the AgNO3 / trGly-H /UO2 (NO3 )2 ·6H2 O system, the composition space diagram approach was employed. The defined crystallization fields of the compounds show that complex 3 is the dominant product, while 4 appears only in a high ligand concentration range. The thermal behavior and solid-state photoluminescence properties of the compounds have been investigated.